Faculty of Pharmacy's vibrant hari raya celebration unites staff in festive spirit / Azlinda Mohamad Nor and Gurmeet Kaur Surindar Singh - Mohamad Nor, Azlinda; Singh, Gurmeet Kaur Surindar (Faculty of Pharmacy, 2024)
On May 10, 2024, the Faculty of Pharmacy at UiTM Puncak Alam came alive with the spirit of Hari Raya Aidilfitri, as staff from all departments gathered for a festive celebration at the Pavillion Hall, UiTM Puncak Alam. The day commenced with enthusiastic staff adorning the booths and hall with vibrant decorations, including traditional ketupat ornaments and twinkling lights, creating a truly festive atmosphere. The staff arrived dressed in their traditional attire, showcasing the rich cultural diversity of the faculty.